If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -2) + 4 = 30 + -3x Reorder the terms: 2(-2 + 3x) + 4 = 30 + -3x (-2 * 2 + 3x * 2) + 4 = 30 + -3x (-4 + 6x) + 4 = 30 + -3x Reorder the terms: -4 + 4 + 6x = 30 + -3x Combine like terms: -4 + 4 = 0 0 + 6x = 30 + -3x 6x = 30 + -3x Solving 6x = 30 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6x + 3x = 30 + -3x + 3x Combine like terms: 6x + 3x = 9x 9x = 30 + -3x + 3x Combine like terms: -3x + 3x = 0 9x = 30 + 0 9x = 30 Divide each side by '9'. x = 3.333333333 Simplifying x = 3.333333333
| 2x+7-3x=25+2x | | 42n-7=13 | | log(2x+3)=1.5 | | 24x^2+112=-184x | | 9*(x-5.3)=8.1 | | 6d+9-3b=2 | | z=z-6 | | 5a+5=15+2-2a | | 8z-13=32-3z | | -8.4(x-3.25)=33.6 | | 224-60x+4x^2=143 | | 4x-3(-3x+y)=18 | | -4.9*x^2+9.8x=-3 | | 3a+5=15+2-1a | | 224-60x+4x^2=80 | | 24t-16=28t-4 | | -8.4(x-3.2)=17.1 | | 3x+4y=240 | | 2x^2+3x+37=x^2 | | 40x=50x | | 4x^2+34x-110=0 | | 7.6(x-2.25)=15.2 | | -2t+4=-2t | | 3a+5=15+2 | | 25x=21x | | n*2-3n-4=0 | | 5-7t=61+t | | 5y+20=3y-6 | | (6x-12)+(2x+12)=180 | | X^2+6x+y^2-10y+3=0 | | 2x+6y=-14 | | 5-7x=61+t |